Are neuroaesthetic principles applied in art therapy protocols for neurorehabilitation? A systematic mini-review - Oliva, Amelia; Iosa, Marco; Antonucci, Gabriella; De Bartolo, Daniela (Frontiers in Psychology, 2023)
Art is an instrument created by man as an alternative way of expression. For this reason, it has also been found use in clinical contexts to improve mood, increase participation in therapy, or improve communication for patients with different pathologies. In this systematic mini-review, we have analyzed the quantitative studies in which art figures as a neurorehabilitation treatment, with the aim of identifying whether standard art therapy protocols exist and whether these are based on the principles of neuro-aesthetics. Our review identified eight quantitative and eighteen qualitative studies that are included as Supplementary material. Although Art Therapy has been used for more than twenty years as a clinical tool, today there are no standard protocols to refer to for planning interventions. Although the effectiveness of using art as therapy has been reported in many qualitative or feasibility studies, there is still a lack of quantitative studies in which outcomes of art therapy are directly based on the principles of neuro-aesthetics.